New analytic criterion for FCC single crystals. (2017) - Cazacu, Oana; Revil-Baudard, Benoit; Chandola, Nitin
Abstract: In this paper a three-dimensional analytical criterion for description of the onset of plastic deformation in cubic single crystals is presented. The criterion is pressure-insensitive and form-invariant to any transformation belonging to the symmetry class of the given crystal. For most FCC single crystals the criterion involves five independent coefficients, which can be determined based on the yield stresses in different crystal orientations. Comparisons with single crystal data on aluminum and copper single crystals show that the criterion can successfully describe the difference in yielding anisotropy between FCC crystals.